Quantitative Analysis of Pravastatin Sodium Polymorphs: a Comparative Study of Chemometric Techniques Combined with Powder X-ray Diffraction, Mid-Infrared, and Raman Spectroscopy - Huang, Yanyan; Liu, Chang; Pan, Hongjuan; Wang, Dong; Wei, Jingjing; Zhong, Jialiang (Pharmaceutical Fronts, 2025)
Pravastatin sodium (PS) is a hydrophilic statin lipid-lowering drug that reduces low-density lipoprotein levels in the blood by inhibiting the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase. It is known to exist in 17 crystalline forms, with some different crystalline forms overlapping in the powder diffraction patterns, making it difficult to control the purity of the crystalline forms. In this study, we aimed to determine the purity of PS crystals using powder X-ray diffraction (PXRD), mid-infrared (MIR) spectroscopy, and Raman techniques. The predictive ability of the partial least squares (PLS) model was constructed and assessed using SPXY, K_S, and Random methods at different partitioning ratios. PLS calibration curves were established based on the relationship between PXRD, MIR, and Raman data and the content of a solid forms of PS (PS-A) in different ranges (full and partial spectra) using different preprocessing algorithms such as multiplicative scattering correction, standard normal variable, Savitzky–Golay filtering, and derivative spectroscopy, or a combination of them. The results showed that the calibration model (y = 0.999x + 0.008 with R2 = 0.999) established using the PXRD method was better, with a low detection limit (1.52%) and quantification limit (4.60%). In addition, by analyzing the testing results of the blind sample, it was found that the confidence intervals of the predicted values of MIR and Raman were wider, indicating a large uncertainty of their parameter estimation. Therefore, it will be better to select the calibration model established by the PXRD method to determine the purity of PS in actual production. This can provide more reliable methodological support for the quality control of pharmaceutical products.
Keywords: pravastatin sodium; quantitative model; PXRD; MIR; Raman